Intraoperative dislocation of the trial bipolar cup into the pelvis during bipolar hip arthroplasty – A case report. (June 2017) - Miyake, Takahito; Kanda, Akio; Morohashi, Itaru; Obayashi, Osamu; Mogami, Atsuhiko; Kaneko, Kazuo
Abstract: Introduction: Bipolar hip arthroplasty is a good option for treating femoral neck fractures, although some contraindications have been indicated. We report a case of intraoperative dislocation of the trial bipolar cup into the pelvis during bipolar hip arthroplasty. Case presentation: A 74-year-old woman underwent bipolar hip arthroplasty for a femoral neck fracture (AO31-B2). She was placed in a lateral decubitus position, and a direct lateral approach was used. During intraoperative trial reduction, the trial bipolar cup became disengaged and dislocated into the anterior space of hip joint. Several attempts to retrieve it failed. The permanent femoral component was inserted, and the wound was closed. The patient was repositioned supine to allow an ilioinguinal approach, and the component was easily removed. She had an uneventful, good recovery. Discussion: Several cases of intraoperative dislocation of the femoral trial head during total hip arthroplasty have been reported, this is the first report of dislocation of a bipolar trial cup. A previous report described difficulty retrieving a trial cup. Conclusion: We easily removed our trial cup using another approach. It is vital to plan systematically for this frustrating complication. Highlights: There have been a few reports of intrapelvic migration of trial femoral heads during total hip arthroplasty, and it is difficult to retrieve from the pelvic space. An additional incision might be useful to retrieve, as might the ilioinguinal approach or sometimes laparotomy. It is important to remove the component based on the patient's condition, component position, and the patient's consent.